Reconstruction of the Limits of Exoneration Clauses in E-Commerce Transactions to Strengthen Consumer Protection Based on Contractual Justice - Esther Masri; Otih Handayani; Ni Luh Gede Astariyani; Farikh Hakimi Jordan; Achmad Jumeri Pamungkas (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Advances in information technology have impacted all business activities, significantly contributing to the world of information and electronic transactions. Electronic buying and selling transactions on electronic commerce (e-commerce) platforms have transformed the legal relationship between businesses and consumers, enabling them to be carried out easily, quickly, and efficiently. In practice, these relationships are often outlined in standard agreements containing exoneration clauses, which limit, transfer, or eliminate the business actor's liability for losses suffered by consumers. This places consumers in an unequal bargaining position, which contradicts the principle of consumer protection. This study aims to analyze the regulation of exoneration clauses in the Indonesian legal system and reconstruct the limits of their use in electronic buying and selling transactions on e-commerce platforms based on the principle of contractual justice to strengthen consumer protection. This study is a normative legal study with a statutory and conceptual approach. The legal sources include primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results indicate that existing regulations do not yet provide clear parameters for distinguishing between reasonable limitations of liability and absolute transfers of responsibility. The proposed reforms include a comprehensive ban on shifting responsibility, strengthening oversight mechanisms, and revoking clauses detrimental to consumers. This reform is expected to create a balance between business interests and consumer rights in e-commerce.